2020
DOI: 10.1177/0300060520928683
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma of the hand with nerve compression

Abstract: Objective This study was performed to analyze the clinical, radiographic, and pathological features of hand angioleiomyoma causing nerve compression and assess the outcomes of surgical excision. Methods This case series included three men and one woman (mean age, 53.3 years; range, 49–56 years). The patients’ chief complaint was numbness of the fingers. The patients’ medical histories were reviewed, and the diagnosis of angioleiomyoma with nerve compression was confirmed by means of imaging examination and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Gupte et al demonstrated that when a linear or branching pattern is seen on T2 weighted and short tau inversion recovery (STIR) sequencing, an angiomyoma should be included in the differential. [22] As stated above, angiomyomas should be considered when soft tissues masses are observed within the upper extremities, and in particular the hands [23][24]. Interestingly, angiomyomas, when found to occur in the hand, are not commonly painful, which could give insight into the pathology and diagnosis [25].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gupte et al demonstrated that when a linear or branching pattern is seen on T2 weighted and short tau inversion recovery (STIR) sequencing, an angiomyoma should be included in the differential. [22] As stated above, angiomyomas should be considered when soft tissues masses are observed within the upper extremities, and in particular the hands [23][24]. Interestingly, angiomyomas, when found to occur in the hand, are not commonly painful, which could give insight into the pathology and diagnosis [25].…”
Section: Discussionmentioning
confidence: 98%
“…As stated above, angiomyomas should be considered when soft tissues masses are observed within the upper extremities, and in particular the hands [ 23 - 24 ]. Interestingly, angiomyomas, when found to occur in the hand, are not commonly painful, which could give insight into the pathology and diagnosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although they often appear as isolated, painless, slow-growing masses, the abundant nerve peripheral occupation region and variable size of the masses can sometimes present with physical symptoms such as nerve deficits or pain. Complete surgical resection is often considered sequelae-free, but in some research, a poor prognosis of neurological deficits has been reported (4)(5)(6)(7).…”
Section: Methodsmentioning
confidence: 99%
“…These tumors arise from vascular smooth muscle, and are typically well circumscribed, usually round or oval in shape [2] . Histologically, angioleiomyomas may present with spindle-shaped smooth cell bundles lacking nuclear atypia arranged in fascicles, arising from the tunica media of a vein or artery [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%